Whole-Genome Approach to Assessing Human Cytomegalovirus Dynamics in Transplant Patients Undergoing Antiviral Therapy - Suárez, Nicolás M.; Blyth, Emily; Li, Kathy; Ganzenmueller, Tina; Camiolo, Salvatore; Avdic, Selmir; Withers, Barbara; Linnenweber-Held, Silvia; Gwinner, Wilfried; Dhingra, Akshay; Heim, Albert; Schulz, Thomas F.; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Human cytomegalovirus (HCMV) is the most frequent cause of opportunistic viral infection following transplantation. Viral factors of potential clinical importance include the selection of mutants resistant to antiviral drugs and the occurrence of infections involving multiple HCMV strains. These factors are typically addressed by analyzing relevant HCMV genes by PCR and Sanger sequencing, which involves independent assays of limited sensitivity. To assess the dynamics of viral populations with high sensitivity, we applied high-throughput sequencing coupled with HCMV-adapted target enrichment to samples collected longitudinally from 11 transplant recipients (solid organ, n=9, and allogeneic hematopoietic stem cell, n=2). Only the latter presented multiple-strain infections. Four cases presented resistance mutations (n=6), two (A594V and L595S) at high (100%) and four (V715M, V781I, A809V and T838A) at low (<25%) frequency. One allogeneic hematopoietic stem cell transplant recipient presented up to four resistance mutations, each at low frequency. The use of high-throughput sequencing to monitor mutations and strain composition in people at risk of HCMV disease is of potential value in helping clinicians implement the most appropriate therapy.